La Vie Saint Jehan-Baptiste a Critical Edition of an Old French Poem of the Early Fourteenth Century. - Gieber, Robert L. (Beihefte Zur Zeitschrift Für Romanische Philologie Ser., 2018)
The book series Beihefte zur Zeitschrift für romanische Philologie is among the most renowned publications in Romance Studies. It covers the entire field of Romance linguistics, including the national languages as well as the lesser studied Romance languages. The series publishes high-quality monographs and collected volumes on all areas of linguistic research, on medieval literature and on textual criticism.